The predictive value of the uric acid/albumin ratio in the phenomenon of coronary slow flow (Annals of Medical Research, 2023)
Aim: Inflammation, oxidative stress, and suboptimal endothelial function have all been implicated in the development of coronary slow flow (CSF) in previous studies. Inflammation has been associated with atherosclerosis, endothelial dysfunction, and microvascular coronary dysfunction. In this situation, it is suspected that albumin and uric acid (UA) are related to the cause of CSF. This study compared the uric acid to albumin ratios (UAR) in coronary arteries with angiographically normal coronary arteries to those in CSF patients.Materials and Methods: In a case-control research, 230 individuals with CSF and an additional 230 individuals who were matched for age, gender, and coronary angiography confirmation to have normal results participated. Retrospective evaluation of 5500 individuals who underwent coronary angiography at our hospital between January 2015 and August 2020 for known or suspected ischemic heart disease was done in this study. Prior to the coronary angiography, our clinic measures basal UA and albumin. By dividing uric acid by albumin, UA/A was calculated. Thrombolysis in Myocardial Infarction Frame Count was used to measure the CSFP.Results: In order to determine UAR, uric acid to albumin was divided. UAR was substantially higher in the CSF group than in the control group (1.180.21 and 1.50.33, respectively, p0.001). We tested whether UAR predicted independently of CSF presence using multiple logistic regression analysis. The cut-off values used by the UA/effective Albumin have sensitivity and specificity of >1,29 and 81% and 70%, respectively, for predicting the presence of CSF. In comparison to uric acid or albumin alone, UAR had a higher diagnostic accuracy to predict CSF (UA AUC:075, albumin AUC:0,552, and UAR AUC:0,826, respectively).Conclusion: We found that patients with CSF had greater levels of UAR than subjects with normal coronary arteries. This was the first study to show that UAR was an independent predictor of CSF.
Keywords: Coronary slow flow phenomenon; Coronary artery disease; Serum uric acid; Albumin